Electric field enhancement and far-field radiation pattern of the nanoantenna with concentric rings - Chen, Shih-Wen (Nanoscale Res Lett, 2014)
The optical antennas have the potential in various applications because of their field enhancement and directivity control. The directivity of a dipole antenna can be improved by directivity-enhanced Raman scattering structure, which is a combination of a dipole antenna and a ring reflector layer on a ground plane. The concentric rings can collect the light into the center hole. Depending upon the geometry of the antenna inside the hole, different electric field enhancements can be achieved. In this paper, we propose to combine the concentric rings with the directivity-enhanced Raman scattering structure in order to study its electric field enhancement and the far-field radiation pattern by finite-difference time-domain simulations. Compared with the structure without the concentric rings over the ground plane, it is found that our proposed structure can obtain stronger electric field enhancements and narrower radiation beams because the gold rings can help to couple the light into the nanoantenna and they also scatter light into the far field and modify the far-field radiation pattern. The designed structures were fabricated and the chemical molecules of thiophenol were attached on the structures for surface-enhanced Raman scattering (SERS) measurements. The measured results show that the structure with concentric rings can have stronger SERS signals. The effects of the dielectric layer thickness in our proposed structure on the near-field enhancements and far-field radiation are also investigated. The proposed structure can be useful for several nanoantenna applications, such as sensing or detecting.